Livelihood Strategies of Rainfed Rice Farmers During the Covid-19 Pandemic in Kalampadu Village, Ogan Ilir Regency - Yulasteriyani, Yulasteriyani; Randi, Randi; Andriani, Dian Sri (Jurnal Masyarakat Maritim, 2025)
The COVID-19 pandemic has profoundly affected rural livelihoods, particularly among rainfed rice farmers whose income heavily depends on seasonal rainfall and market access. This study explores the livelihood strategies adopted by rainfed rice farmers in Kalampadu Village, Ogan Ilir Regency, during the pandemic era. The research aims to identify how farmers adapted their agricultural and non-agricultural activities in response to declining productivity, market disruptions, and mobility restrictions. Using a qualitative descriptive approach, data were collected through in-depth interviews, field observations, and documentation involving 25 farming households. The analysis applied the Sustainable Livelihood Framework (SLF) to assess changes in five livelihood assets: human, natural, physical, financial, and social capital. The findings indicate that farmers experienced significant income reduction due to unstable rainfall patterns and limited access to agricultural inputs. To cope, they diversified their income sources through wage labor, small-scale trading, livestock rearing, and social network-based cooperation. Social capital played a crucial role in maintaining food security and sustaining mutual aid systems such as “gotong royong.” Furthermore, women contributed to household resilience by engaging in home-based economic activities, including food processing and handicrafts. The government’s social assistance programs and local institutions’ support were identified as key external factors enhancing adaptive capacity. This study concludes that livelihood sustainability among rainfed farmers during the pandemic relied on a combination of diversification, adaptation, and social collaboration. Strengthening local institutional capacity and promoting climate-resilient agricultural practices are recommended to enhance future livelihood resilience in rural communities vulnerable to environmental and economic shock